Effect of the π-linker on the performance of organic photovoltaic devices based on push–pull D–π–A molecules. (12th June 2018) - Lim, Hong Chul; Kim, Jang-Joo; Jang, Jyongsik; Hong, Jong-In
Abstract : The bulk heterojunction organic photovoltaic (OPV) devices based on3T : PC71 BM (2 wt%, 1 : 1.75 w/w) exhibited a higher power conversion efficiency of 2.58% thanDTT -based OPV devices. Abstract : Two push–pull D–π–A molecules, 3T andDTT as donor materials, were synthesized and characterized for solution-processed bulk heterojunction (BHJ) organic photovoltaic (OPV) devices. The π-linker plays a vital role not only in electrochemical and thermal properties but also affects the thin film morphology of3T andDTT .3T showed the high electrochemical stability with a faster electrode reaction rate. The solution-processed OPV devices based on3T showed higher power conversion efficiencies thanDTT -based devices because of its superior electrochemical properties.